Antibacterial activity and biocompatibility of zein scaffolds containing silver-doped bioactive glass. (24th August 2018) - El-Rashidy, Aiah A; Waly, Gihan; Gad, Ahmed; Roether, Judith A; Hum, Jasmin; Yang, Yuyun; Detsch, Rainer; Hashem, Azza A; Sami, Inas; Goldmann, Wolfgang H; Boccaccini, Aldo R
Abstract: Composite 3D scaffolds combining natural polymers and bioceramics are promising candidates for bone tissue engineering (BTE). Zein, as a natural plant protein, offers several advantages, including biocompatibility, adequate strength properties, and low/no immunogenicity; however, it lacks bioactivity. Thus, composite zein: bioactive glass (BG) scaffolds are proposed as promising candidate for BTE applications, with silver-doping of bioactive glass providing an antibacterial effect against possible post-implantation infection. Therefore, the aim of this study was to investigate the in vitro antibacterial properties, biocompatibility, bioactivity and compressive strength of zein scaffolds containing silver-doped bioactive glass. BG nanoparticles, undoped and Ag-doped, were fabricated using the sol-gel method. 3D composite zein:BG scaffolds, containing 20 wt% BG, were prepared and their antibacterial activity against Escherichia coli (E. coli) and Staphylococcus aureus (S. aureus) was assessed using the disc diffusion assay. Human osteoblast-like MG-63 cells were used to evaluate the in vitro biocompatibility of the prepared scaffold groups. In addition, the compressive strength of the scaffolds was determined using uniaxial compression strength testing and the scaffold interconnected porosity was measured using helium pycnometer. Disc diffusion assay showed that only zein scaffolds containing Ag-doped sol-gel BG are antibacterially positive against E. coli and S. aureus . Pure zein scaffolds and zein scaffolds containing sol-gel-derived BG showed no negative influence on the growth of MG-63 cells, as evident by the cells' ability to survive, proliferate, and function on these scaffolds. Moreover, incorporating sol-gel-derived BG into zein scaffolds at zein:BG of 80:20 ratio showed bioactive properties with adequate porosity without affecting the scaffolds' compressive strengths, which was similar to that of trabecular bone, suggesting that the new composites have potential for BTE applications in non-loaded bearing areas.